(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
The article reveals the changes affecting the training of future teachers in the context of the introduction of the professional standard of the teacher. The authors identify the features of the practical training of students – future teachers and consider the possibilities of strengthening the practice-oriented training of students at a pedagogical university, which is the purpose of the study. The experience of organizing and conducting educational and industrial practices with students of a pedagogical university has shown that in addition to the traditional guidance of practice by university teachers, it is necessary to create tools for psychological and pedagogical support of students during the practice period: schemes of planning and analysis of activities, diagnostic materials, descriptions of technologies, methods, teaching and upbringing techniques, bibliography on various problems, related to professional activity, links to generally recognized professional and educational portals, creating a piggy bank of pedagogical ideas. The availability of such tools allows students to feel more confident and independently manage their professional activities within the framework of solving professional tasks implemented in practice. Thus, practical training has the capabilities that are necessary in the professional development of a future teacher, allows the student to try his hand at the chosen profession, learn how to apply the knowledge gained in the classroom, in professional activities. However, the realization of these opportunities requires a number of organizational and pedagogical conditions associated with updating the content of practical training and its focus on the development of general professional and professional competence of students; the search and implementation of new approaches to the organization and evaluation of practical training of future teachers; providing a supportive educational and professional environment. An important condition for the success of practical training of university students is the readiness of university teachers to implement their professional tasks.